2003
DOI: 10.1046/j.1523-1747.2003.12042.x
|View full text |Cite
|
Sign up to set email alerts
|

Visualization and Characterization of Migratory Langerhans Cells in Murine Skin and Lymph Nodes by Antibodies Against Langerin/CD207

Abstract: Dendritic cells are professional antigen-presenting cells that initiate primary immunity. Migration from sites of antigen uptake to lymphoid organs is crucial for the generation of immune responses. We investigated the migratory pathways specifically of epidermal Langerhans cells by tracing them from the epidermis to the draining lymph nodes. This was possible with a new monoclonal antibody, directed against murine Langerin/CD207, a type II lectin specific for Langerhans cells. In situ, resident, and activated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
143
2
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 158 publications
(160 citation statements)
references
References 53 publications
(69 reference statements)
13
143
2
2
Order By: Relevance
“…Shibaki et al (29) used mice expressing the whole OVA protein under the K14 promoter and showed that DCs emigrating from skin explants cross-presented OVA peptides. DCs emigrating from whole skin explants are a mixture of dermal DCs and LCs (30), and therefore, the relative contribution of LCs could not be determined in this report. In the second report by Mayerova et al (31), LCs were sorted from skin draining lymph nodes of mice expressing SIINFEKL under the K14 promoter.…”
Section: Discussionmentioning
confidence: 92%
“…Shibaki et al (29) used mice expressing the whole OVA protein under the K14 promoter and showed that DCs emigrating from skin explants cross-presented OVA peptides. DCs emigrating from whole skin explants are a mixture of dermal DCs and LCs (30), and therefore, the relative contribution of LCs could not be determined in this report. In the second report by Mayerova et al (31), LCs were sorted from skin draining lymph nodes of mice expressing SIINFEKL under the K14 promoter.…”
Section: Discussionmentioning
confidence: 92%
“…Henri et al (34) have demonstrated that the numbers of Langerin-positive cells in LNs draining the skin are normally regulated by a steady state of migration, consistent with the presence of some Langerin/CD207-positive cells in the control LNs. In addition, Stoitzner et al (35) have shown that Langerin/CD207-positive cells in the skin-draining LNs are mostly mature. Changes in LC numbers in both the ear epidermis and draining LNs were consistent with IgE-mediated mast cell activation inducing LC migration in the context of a background level of continuous recruitment of immature LC to the skin and subsequent migration of cells to the draining LNs.…”
Section: Discussionmentioning
confidence: 99%
“…Skins were cultured in 24-well plates, as described (16), in the presence of CGRP and/or MIP-3b for 72 h, and the cells that migrated into the culture medium (RPMI 1640 supplemented with 10% FCS, 0.02 mM kanamycin, and 5 mM 2-ME) were counted.…”
Section: Skin Explant Culture Assaymentioning
confidence: 99%
“…After applying a hapten, activated LCs migrated from the epidermis to the dermis and then to the draining LNs, wherein they induced T cell sensitization (16). To determine whether CGRP could affect Langerin + cell migration at the sensitization phase of CHS, we examined the effect of CGRP on the number of Langerin + cells that migrated to the draining LNs.…”
Section: Cgrp Inhibits Langerin + Cell Migration In the Tncb-chs Respmentioning
confidence: 99%